Judicial System in Cambodia: A Documentary Data Analysis from 2018 to 2021 - KONG, Sopheak; SOEU, Sovannakpheach; ROS, Ravuth; DY, Putheara (MASI Mandiri Edukasi, 2024)
This study uses documentary research methods to thoroughly examine how the Cambodian court has changed over time, the problems it faces now, and the possible solutions that have been suggested. The study tells the story of Cambodia's court system from colonization to today, focusing on important events and ongoing problems. It uses rules, laws, old records, government reports, and survey numbers. According to structured research, the piece gives information about things that have been done, like setting up courts nationwide and settling criminal cases. The piece also discusses problems like insufficient people to work as judges, inadequate infrastructure, and no rules governing specific judicial jobs. This part of the research approach explains the video analysis strategy used in this study. This makes the research process more open and rigorous.